Evaluation of the efficacy of cysteamine cream compared to hydroquinone in the treatment of melasma: A randomised, double‐blinded trial. (27th September 2020) - Nguyen, Jennifer; Remyn, Laura; Chung, In Young; Honigman, Anthony; Gourani‐Tehrani, Shima; Wutami, Ilycia; Wong, Celestine; Paul, Eldho; Rodrigues, Michelle
Abstract: Background/Objective: Melasma is a commonly acquired disorder of hyperpigmentation that often poses a therapeutic challenge for dermatologists. Recently, cysteamine cream has shown promising results compared to placebo. This study aims to determine the efficacy of cysteamine cream compared to hydroquinone cream in the treatment of melasma. Methods: A randomised, double‐blinded, single‐centre trial was conducted in Victoria, Australia. 20 recruited participants were given either cysteamine cream or hydroquinone cream for 16 weeks. The primary outcome measure was a change in the modified Melasma Area and Severity Index (mMASI). Quality of life at baseline and week 16 as well as standard digital photography at each follow‐up visit was assessed as secondary outcome measures. Results: At week 16, 14 participants completed the study with 5 participants in the cysteamine group and 9 patients in the hydroquinone group. In the intention to treat analysis, there was a 1.52 ± 0.69 (21.3%) reduction in mMASI for the cysteamine group and a 2.96 ± 1.15 (32%) reduction in the hydroquinone group. The difference between groups was not statistically significant ( P  = 0.3). Hydroquinone cream was generally better tolerated that cysteamine cream. Conclusion: Our study suggests that topical cysteamine may have comparable efficacy to topical hydroquinone. Cysteamine thus provides a possible alternative to patients and clinicians who wish to avoid or rotate off topical hydroquinone. While side effects were more common for participants using cysteamine compared with hydroquinone, these were mild and reversible. Larger studies comparing cysteamine and hydroquinone are required to support these findings.